Antidepressant-like activity of a brain penetrant HCN channel inhibitor in mice - Pinares-Garcia, Paulo; Spyrou, James; McKenzie, Chaseley E.; Forster, Ian C.; Soh, Ming S.; Mohamed Syazwan, Erlina; Atif, Mohammed; Reid, Christopher A. (Frontiers in Pharmacology, 2023)
Changes in Hyperpolarization-Activated Cyclic Nucleotide-Gated (HCN) channel function have been linked to depressive-like traits, making them potential drug targets. However, there is currently no peer-reviewed data supporting the use of a small molecule modulator of HCN channels in depression treatment. Org 34167, a benzisoxazole derivative, has been patented for the treatment of depression and progressed to Phase I trials. In the current study, we analysed the biophysical effects of Org 34167 on HCN channels in stably transfected human embryonic kidney 293 (HEK293) cells and mouse layer V neurons using patch-clamp electrophysiology, and we utilised three high-throughput screens for depressive-like behaviour to assess the activity of Org 34167 in mice. The impact of Org 34167 on locomotion and coordination were measured by performing rotarod and ledged beam tests. Org 34167 is a broad-spectrum inhibitor of HCN channels, slowing activation and causing a hyperpolarising shift in voltage-dependence of activation. It also reduced Ih-mediated sag in mouse neurons. Org 34167 (0.5 mg/kg) reduced marble burying and increased the time spent mobile in the Porsolt swim and tail suspension tests in both male and female BALB/c mice, suggesting reduced depressive-like behaviour. Although no adverse effects were seen at 0.5 mg/kg, an increase in dose to 1 mg/kg resulted in visible tremors and impaired locomotion and coordination. These data support the premise that HCN channels are valid targets for anti-depressive drugs albeit with a narrow therapeutic index. Drugs with higher HCN subtype selectivity are needed to establish if a wider therapeutic window can be obtained.